Radio Frequency Identification: Security and Privacy Issues 6th International Workshop, RFIDSec 2010, Istanbul, Turkey, June 8-9, 2010, Revised Selected Papers - Ors Yalcin, Siddika Berna; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th International Workshop Radio Frequency Identification: Security and Privacy Issues. RFIDSec 2010, held in Istanbul, Turkey, in June 2010. The 17 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 47 submissions. The papers focus on approaches to solve security and data-protection issues in advanced contactless technologies like RFID. Topics addressed are new applications for secure RFID systems, data protection and privacy-enhancing techniques for RFID, cryptographic protocols for RFID, integration of secure RFID systems, resource-efficient implementation of cryptography, attacks on RFID systems, and RFID security hardware.
Invited Talk 1 -- The Physical Basis of RFID Security -- Session 1 -- Still and Silent: Motion Detection for Enhanced RFID Security and Privacy without Changing the Usage Model -- Cryptanalysis of the David-Prasad RFID Ultralightweight Authentication Protocol -- Practical NFC Peer-to-Peer Relay Attack Using Mobile Phones -- Strong Authentication and Strong Integrity (SASI) Is Not That Strong -- Invited Talk 2 -- Privacy Models for RFID Schemes -- Session 2 -- On the Claimed Privacy of EC-RAC III -- EC-RAC: Enriching a Capacious RFID Attack Collection -- Anonymous RFID Authentication Using Trusted Computing Technologies -- Tree-Based RFID Authentication Protocols Are Definitively Not Privacy-Friendly -- Invited Talk 3 -- Hardware Intrinsic Security -- Session 3 -- Privacy-Preserving Pattern Matching for Anomaly Detection in RFID Anti-Counterfeiting -- Time Measurement Threatens Privacy-Friendly RFID Authentication Protocols -- Anonymous Authentication for RFID Systems -- Leakage-Resilient RFID Authentication with Forward-Privacy -- Session 4 -- An ECDSA Processor for RFID Authentication -- Towards a Practical Solution to the RFID Desynchronization Problem -- Session 5 -- Optimal Security Limits of RFID Distance Bounding Protocols -- The Poulidor Distance-Bounding Protocol -- A Lightweight Implementation of Keccak Hash Function for Radio-Frequency Identification Applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Systems and Data Security; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Special Purpose and Application-Based Systems